Role of CCR2+ Myeloid Cells in Inflammation Responses Driven by Expression of a Surfactant Protein-C Mutant in the Alveolar Epithelium - Venosa, Alessandro; Cowman, Sophie; Katzen, Jeremy; Tomer, Yaniv; Armstrong, Brittnie S.; Mulugeta, Surafel; Beers, Michael F. (Frontiers in Immunology, 2021)
Acute inflammatory exacerbations (AIE) represent precipitous deteriorations of a number of chronic lung conditions, including pulmonary fibrosis (PF), chronic obstructive pulmonary disease and asthma. AIEs are marked by diffuse and persistent polycellular alveolitis that profoundly accelerate lung function decline and mortality. In particular, excess monocyte mobilization during AIE and their persistence in the lung have been linked to poor disease outcome. The etiology of AIEs remains quite uncertain, but environmental exposure and genetic predisposition/mutations have been identified as two contributing factors. Guided by clinical evidence, we have developed a mutant model of pulmonary fibrosis leveraging the PF-linked missense isoleucine to threonine substitution at position 73 [I73T] in the alveolar type-2 cell-restricted Surfactant Protein-C [SP-C] gene [SFTPC]. With this toolbox at hand, the present work investigates the role of peripheral monocytes during the initiation and progression of AIE-PF. Genetic ablation of CCR2+ monocytes (SP-CI73TCCR2KO) resulted in improved lung histology, mouse survival, and reduced inflammation compared to SP-CI73TCCR2WT cohorts. FACS analysis of CD11b+CD64-Ly6Chi monocytes isolated 3 d and 14 d after SP-CI73T induced injury reveals dynamic transcriptional changes associated with “Innate Immunity’ and ‘Extracellular Matrix Organization’ signaling. While immunohistochemical and in situ hybridization analysis revealed comparable levels of tgfb1 mRNA expression localized primarily in parenchymal cells found nearby foci of injury we found reduced effector cell activation (iNOS, Arg1) in SP-CI73TCCR2KO lungs as well as partial colocalization of tgfb1 mRNA expression in Arg1+ cells. These results provide a detailed picture on the role of resident macrophages and recruited monocytes in the context of AIE-PF driven by alveolar epithelial dysfunction.